Health related quality of life among people with mental illness: The role of socio-clinical characteristics and level of functional disability - Defar, Semira; Abraham, Yacob; Reta, Yared; Deribe, Bedilu; Jisso, Meskerem; Yeheyis, Tomas; Kebede, Kurabachew Mengistu; Beyene, Bereket; Ayalew, Mohammed (Frontiers in Public Health, 2023)
Background: People with mental illness (PWMI) have declining health-related quality of life (HRQoL), which is frequently equivalent to or greater than that of medical disorders. Although HRQoL is rapidly being recognized as an essential treatment outcome indicator in modern psychiatry, research on the identification and significance of factors impacting QoL in PWMI is still in its early stages. Objective: The aim of this study was to identify predictors of HRQoL among people with mental illness who underwent outpatient follow-up in Sidama region, southern Ethiopia. Methods: We conducted a multicenter, cross-sectional study from April-1, to May-30, 2022. A total of 412 participants took part in the study, using an interviewer-administered structured questionnaire. The HRQoL was measured using the 12-item Short-Form Health Survey-Version 2 (SF-12v2) scale. To describe different variables, descriptive statistics were employed. To find independent HRQoL predictors, we used multivariable linear regression analysis. A P-value of <0.05 was declared statistically significant at 95% confidence interval (CI). Result: Out of 412 participants, nearly two-third 261(63.3%) were male and nearly half 203(49.3%) were diagnosed as schizophrenia. HRQoL was positively associated with social support (β=0.321) and being single (β=2.680). Conversely, functional disability (β =-0.545), being a student (β =-4.645) and jobless (β =-3.279) by occupation, and being diagnosed with depression (β =-2.839) were negatively impacted HRQoL among PWMI. Conclusion: HRQoL of people with mental disorders in this study was significantly associated with social support, marital status, occupation, diagnosis, and level of functional disability. Therefore, the mental health care system should develop HRQoL promoting measures that enhance PWMI functioning, social support, and employment.